HOW CAN THE EPIKARST ZONE INFLUENCE THE KARST AQUIFER HYDRAULIC BEHAVIOUR? - Trček B. (My University, 2007)
The role of an epikarst zone in the karst aquifer hydraulic behaviour was brought into focus in our studies referring to the catchment area of the Hubelj spring (SW Slovenia). This study points out the significance of effects of the fast preferential flow—epiflow, which is the main factor controlling solute/contaminant transport towards the aquifer saturated zone. The so-called epikarstic hypothesis is verified on the basis of the most significant research results that are supported by the most important findings from the literature.
Keywords: KARST AQUIFER; EPIKARST ZONE; HYDRAULIC BEHAVIOUR; NATURAL TRACERS; SLOVENIA